Redesign of the CDNH Portal - Jovanov, Mile; Mihova, Marija; Ackovska, Nevena; Markovski, Smile (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2010)
The main role of the Center for Digitization of National Heritage (CDNH) at the Institute of Informatics is to produce digital presentations of the cultural heritage elements and make them available on the web, through the portal of CDNH. This portal has been developed during the last four years, and this year we introduced a completely new design. In this paper we present the growth and the services that were offered by the old portal and the needs for the new design. We will also present the new offered features.
Keywords: digitization, CDNH Macedonia, national heritage presentation